MICHAEL W. MEHAFFY - Cities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban Renaissance - Monclús Fraga, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Michael W. Mehaffy Cities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban RenaissancePortland, Oregon (USA): Sutasis Press, 2017. 288 pp. Softcover. Language: English. 19 €ISBN: 978-9463864046